SISTEM PEMBUKTIAN TERBALIK (SHIFTING THE BURDEN OF PROOF) MENURUT UU NO 20 TAHUN 2001 JO UU NO 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Atet Sumanto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
That inversed verification according to UU No. 20 Year 2001 Jo UU No. 31 Year 1999 having the character of is limited, and proportional, its meaning of defendant have the right to prove that he do not corruption doing an injustice; That besides defendant have the right to prove, he obliged to give boldness about entire/all it’s good and chattel and consort estae, child, and good and chattel each; every people/or anticipated corporation have link with case.